2019
DOI: 10.3390/s19030561
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Fuzzy-Logic-Based Clustering Technique for Hierarchical Routing Protocols in Wireless Sensor Networks

Abstract: In wireless sensor networks, the energy source is limited to the capacity of the sensor node’s battery. Clustering in WSN can help with reducing energy consumption because transmission energy is related to the distance between sender and receiver. In this paper, we propose a fuzzy logic model for cluster head election. The proposed model uses five descriptors to determine the opportunity for each node to become a CH. These descriptors are: residual energy, location suitability, density, compacting, and distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 54 publications
0
79
0
1
Order By: Relevance
“…Hamzah et al [33] proposed a fuzzy logic-based energy-efficient clustering for wireless sensor networks on the basis of minimum separation distance imposition between cluster heads. In this work, the authors emphasized the fact that if the clustering algorithm exploits more energy affecting factors, then the clustering will be more efficient.…”
Section: Fuzzy Logic-based Wsn Clusteringmentioning
confidence: 99%
“…Hamzah et al [33] proposed a fuzzy logic-based energy-efficient clustering for wireless sensor networks on the basis of minimum separation distance imposition between cluster heads. In this work, the authors emphasized the fact that if the clustering algorithm exploits more energy affecting factors, then the clustering will be more efficient.…”
Section: Fuzzy Logic-based Wsn Clusteringmentioning
confidence: 99%
“…In TL‐LEACH as an extension to LEACH protocol, the mechanism for rotating the cluster head role is modified to better distribute the energy consumption in the network. Hamzah et al utilized the fuzzy logic based on minimum separation distance to select the best cluster head in each round. In Sasikumar and Khara, two centralized and distributed k ‐means clustering algorithm is implemented as an alternative to the LEACH‐based protocols. From the perspective of energy efficiency mechanism, three distinct directions in the research works can be identified: sensor lifetime enhancement, load balancing, and network lifetime maximization.…”
Section: Related Workmentioning
confidence: 99%
“…Hamzah et al [10] proposed the Fuzzy Logic-based Energy-Efficient Clustering for WSNs based on the minimum partition Distance (FL-EEC/D) enforcement between CHs. In this protocol, the Gini index was considered for measuring the clustering algorithm's energy efficiency in terms of their ability to balance the allocation of power via sensor nodes.…”
Section: Literature Surveymentioning
confidence: 99%